Nutritional status of coriander under fertigation depths and pulse and continuous drip irrigation - Sirleide M. de Menezes; Gerônimo F. da Silva; Valentin R. Ó. Zamora; Manassés M. da Silva; Anna C. R. A. da Silva; Ênio F. de F. e Silva (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to evaluate the nutritional status of coriander cultivar Verdão under fertigation depths and pulse and continuous drip irrigation. The experiment was conducted in a protected environment at the Universidade Federal Rural de Pernambuco, Recife, PE, Brazil (8° 1’ 6.50” S, 34° 56’ 46” W and altitude of 6.5 m), in the randomized block design in 2 x 5 factorial scheme, with three repetitions. Treatments consisted of five irrigation depths (40, 60, 80, 100 and 120% of crop evapotranspiration - ETc) and two types of fertigation application (pulse and continuous). At 27 days after sowing, the aerial part of 48 plants per plot was collected for subsequent quantification of nitrogen, phosphorus, potassium, calcium, magnesium, sulfur, iron, manganese, copper and zinc concentrations. Pulse fertigation combined with ETc replacement depths below 100% promoted higher leaf concentrations of phosphorus, sulfur, iron and manganese. Continuous fertigation combined with 100% ETc depth induced sulfur deficiency in the crop and, combined with 40% ETc depth, promoted the highest calcium concentration. Regardless of the type of application, ETc replacement depths from 82.7 and 40% provide adequate leaf concentrations of nitrogen and magnesium, respectively. Regardless of the applied depth, pulse fertigation reduced the leaf concentrations of magnesium.